EARNING MANAGEMENT'S, FIXED ASSET INTENSITY'S EFFECT ON TAX MANAGEMENT WITH MANAGEMENT COMPENSATION AS INTERVERNING VARIABLE - Wenten, I Ketut; Doaly, Thom Deutmar Londo; Barly, Harry (Jurnal Mebis, 2023)
This study aims to examine and analyze the effect of earnings management and fixed asset intensity on tax management with management compensation as an intervening variable in primary consumer goods manufacturing companies. The data source used in this study is secondary data in the form of published company financial reports. In this study, the population consisted of 76 primary consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Meanwhile, the determination of the research sample used a purposive sampling method in order to obtain sample data of 64 companies or 120 research sample data. The analytical method used in this study is the panel data linear regression method and the data analysis technique used in this study is an application named eviews 10. The results show that partially earnings management has a significant effect on tax management, but asset intensity still has no effect on management tax. And simultaneously earnings management and fixed asset intensity affect tax management. Management compensation can mediate the effect of Earnings Management on Tax Management, but management compensation cannot mediate the effect of fixed asset intensity on tax management.